The impact of coronary microvascular dysfunction on the discordance between fractional flow reserve and resting full-cycle ratio in patients with chronic coronary syndromes - Legutko, Jacek; Niewiara, Lukasz; Guzik, Bartlomiej; Szolc, Piotr; Podolec, Jakub; Nosal, Marcin; Diachyshyn, Marta; Zmudka, Krzysztof; Kleczynski, Paweł (Frontiers in Cardiovascular Medicine, 2022)
Background Resting full-cycle ratio (RFR) is an alternative to fractional flow reserve (FFR) for the evaluation of borderline coronary artery lesions. Although FFR and RFR results are discordant in some cases, factors associated with the discordance remain unclear. The role of coronary microvascular dysfunction (CMD) is discussed as a potential mechanism to explain these discrepancies. Aim The study aimed to assess concordance between RFR and FFR in a real-life cohort from a high-volume center regarding the role of CMD. Methods Consecutive patients with borderline coronary lesions undergoing coronary functional testing for chronic coronary syndromes were included in the study. Measurements of RFR and FFR were performed alongside additional coronary flow reserve (CFR), resistance reserve ratio (RRR), and an index of microcirculatory resistance (IMR) measurements. CMD was defined according to the current guideline by either IMR ≥25 or CFR ≤2.0 in vessels with no significant stenosis. Results Measurements were performed in 157 coronary arteries, in 101 patients, with a median age of 66 y., 74% male, with prior history of arterial hypertension (96%), dyslipidaemia (91%), and diabetes (40%). The median value of vessel diameter stenosis was 45% according to QCA. Overall, FFR and RFR values were significantly correlated (r = 0.66, p < 0.001), where positive FFR/negative RFR and negative FFR/positive RFR were observed in 6 (3.8%) and 38 (24.2%) of 157 vessels. The RFR/FFR discrepancy was present in 44 (28%) of measurements. CMD was confirmed in 28 (64%) of vessels with discrepant RFR/FFR and in 46 (41%) of vessels with concordant results (p = 0.01). In discordant RFR/FFR vessels, as compared to concordant ones, significantly lower values of CFR [median 1.95 (IQR: 1.37, 2.30) vs. 2.10 (IQR: 1.50, 3.00), p = 0.030] and RRR [median 2.50 (IQR: 1.60, 3.10) vs. 2.90 IQR (1.90, 3.90), p = 0.048] were observed. Main predictors of RFR/FFR discrepancy in a univariate regression analysis were: higher age of patients [OR = 1.06 (1.01; 1.10), p = 0.010], presence of CMD [OR = 2.51 (1.23; 5.25), p = 0.012], lower CFR [OR = 1.64 (1.12; 2.56), p = 0.018], and lower RRR values [OR = 1.35 (95% CI: 1.03; 1.83), p = 0.038]. Conclusion In discrepant RFR/FFR vessels, CMD is more prevalent than in concordant RFR/FFR measurements, which can be driven by lower CFR or RRR values. Further research is needed to confirm this observation.